Outcome of cephalo-medullary nailing in intertrochanteric fracture of femur - Kumar, Sah Rabins; Gaurav, Gupta (International Journal of Research in Orthopaedics, 2022)
Background: Intertrochanteric fracture is commonly seen in elderly and osteoporotic bone due to trivial trauma and requires hospitalization. Nonoperative treatment leads to complications like bedsore, pneumonia and deep vein thrombosis. The introduction of cephalomedullary nailing has broadened its use in complex intertrochanteric fracture with least complications. Methods: A prospective observational study was conducted in Birgunj, Nepal from 4th October 2020 to 3rd October 2021 among 50 patients of age more than 30 years with closed intertrochanteric fractures. Ethical approval was obtained from the institutional review committee and proper informed consent was taken. Modified Harris hip scoring system was used. Type of implant used was PFN long and short. Results: The mean age of 50 patients was 66.42 years, female to male ratio was 1.5:1 (30:20) and right side (72%) with fall injury (78%) was commonly observed. According to Kyles classification, 40% patients had Kyles’s type II fracture followed by type III (38%). Most of the cases start mobilization on 2nd post operative day. Mean Harris hip score at 14 days, 6 weeks, 3 months and 6 months were 52.02, 64.50, 72.91 and 84.40 respectively. Early mobilization within 2 days of post-surgery had significant improvement in functional outcome throughout follow up as compared to more than 2 days (p=0.001, 0.001, 0.001 and 0.001 at 14 days, 6 weeks, 3 months and 6 months respectively). Radiological union was achieved in all cases within 6 months. Conclusions: The study results concluded cephalomedullary nailing is effective treatment for intertrochanteric fracture.